Study on the Damping Effect of Particle Dampers considering Different Surface Properties - Xiaowei Li; Yue Yang; Weixing Shi (Shock and Vibration)
Particle dampers are nonlinear vibration control devices. The surface property has a great influence on the performance of the particle damper, but it is difficult to be considered and analyzed. This paper firstly gives a view of how to establish a theoretic model of the particle damper. The dynamic equation and energy dissipation coefficient of collision are revised from the Hertz contact theory in the proposed theoretic model, considering the friction of particles. Then, a contrastive collision model relying on the finite element method is established to verify the reasonability of the theoretic model. The effects of different factors which will have an influence on the performance of the particle damper are discussed, and several conclusions on how to optimize the particle damper are proposed. Except for the aforementioned dynamic analysis, this paper also presents a particle damping index to evaluate the capability of energy dissipation of different materials, in order to facilitate the material selection in the practical design. Finally, an experiment is developed to verify the character of the collision and energy dissipation. The feasibility of the proposed method to estimate the surface property of different particles is validated by the free vibration experiment.